2015
DOI: 10.3390/life5010538
|View full text |Cite
|
Sign up to set email alerts
|

A Prokaryotic Twist on Argonaute Function

Abstract: Argonaute proteins can be found in all three domains of life. In eukaryotic organisms, Argonaute is, as the functional core of the RNA-silencing machinery, critically involved in the regulation of gene expression. Despite the mechanistic and structural similarities between archaeal, bacterial and eukaryotic Argonaute proteins, the biological function of bacterial and archaeal Argonautes has remained elusive. This review discusses new findings in the field that shed light on the structure and function of Argona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 76 publications
1
25
0
1
Order By: Relevance
“…MjAgo anchors the 5'-and 3'-end of a canonical guide strand in dedicated binding pockets in the Mid and PAZ domain, respectively (PDB: 5G5S and 5G5T). 1,24 We tested whether mutations in the functional domains of MjAgo (Figure 4a) affect the plasmid cleavage activity. PAZ binding pocket mutants (Y194A, H213A, Y217A, E246A)…”
Section: Mutational Analysis Of Mjago-mediated Non-canonical Dna Subsmentioning
confidence: 99%
See 1 more Smart Citation
“…MjAgo anchors the 5'-and 3'-end of a canonical guide strand in dedicated binding pockets in the Mid and PAZ domain, respectively (PDB: 5G5S and 5G5T). 1,24 We tested whether mutations in the functional domains of MjAgo (Figure 4a) affect the plasmid cleavage activity. PAZ binding pocket mutants (Y194A, H213A, Y217A, E246A)…”
Section: Mutational Analysis Of Mjago-mediated Non-canonical Dna Subsmentioning
confidence: 99%
“…Argonaute (Ago) proteins are crucially involved in RNA-guided or DNA-guided degradation of target nucleic acids. [1][2][3] Present in all three domains of life, they bind guide strands in vivo to target complementary nucleic acids. Eukaryotic Agos interact with cytoplasmic RNA substrates 18-23 bp in length [4][5][6] while prokaryotic Agos (pAgos) bind and process a variety of DNA and RNA substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between prokaryotic AGO orthologs and both sRNA and DNA fragments were recently documented (37), and, interestingly, the sizes of DDB2-associated DNA fragments are in the median size-range of excised DNA released during NER in prokaryotes (12 nt to 13 nt) and eukaryotes (38) (25 nt to 30 nt). Moreover, prokaryotic and eukaryotic AGOs are structurally similar to RNase H, possibly enabling DNA/RNA duplex formation for DNA processing (39) whereas, in Tetrahymena thermophile, AGO-related proteins loaded with Dicerdependent sRNAs promote physical DNA elimination during macronucleus development (40). Nonetheless, nuclear Ago2 interacts with sRNAs but not DNA following ionizing radiation of human cells (41), suggesting that nuclear Ago-bound nucleic acids may vary depending on the organism and DNA repair process involved.…”
Section: Nuclear Pools Of Ptgs-related Agos and Interactions Of Agos mentioning
confidence: 99%
“…Indeed, intriguingly, in vitro, prokaryotic Agos display a greater affinity for short DNA molecules than for RNA 6 . Most strikingly, bacterial Agos have been lately shown to associate and cleave single-strand DNA in vivo, using both sRNA and DNA fragments as guide molecules 8,11,12 . Furthermore, it has been recently reported that AGO2 interacts with RAD51, a DNA repair factor involved in homologous recombination (HR), and mediates its accumulation at resected DNA damage sites in human cells 13 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Among the RNAi components, members of Argonaute (Ago) family of proteins play a fundamental role, acting as the effectors of sRNA-mediated gene silencing 6 . Ago proteins (Agos in brief) are evolutionary conserved in each of the three domains of life; indeed, all eukaryotic genomes, with the exception of S. cerevisiae, and many prokaryotic ones, encode for Agos [6][7][8] . During the last decade, besides their well-established cytoplasmic role in post-transcriptional gene silencing, novel functions for eukaryotic Agos have been described to impact in different ways on gene expression, also by acting in the nucleus 7 .…”
Section: Please Scroll Down For Articlementioning
confidence: 99%